Planning of the management of safety and health at work in the public universities of the District of Riohacha department of the Guajira, Colombia (GEON Journal (Management, Organizations and Business), 2020)
The present work derives from an investigation whose main purpose was to analyze the Management of Safety and Health at Work in the Public Universities of the District of Riohacha in La Guajira, Colombia. Theoretically, it was based on authors from the area of ​​Safety and Health at Work, such as, Law 1072 of (2015), Chiavenato (2007), Münch and García (2008). Regarding its methodology, this work was descriptive, non-experimental, cross-sectional and field-based. Its population was made up of 2 universities in the public sector, located in the District of Riohacha. To collect the information, a questionnaire consisting of 57 Likert-type scale questions was used. In relation to the results obtained, it was concluded that regarding the variable occupational health and safety, it is necessary to use administrative planning tools to consolidate the communication channels established within the organization, in the same way, to encourage staff that works in order to improve its performance. It is also suggested that they exhaustively promote the implementation and use of personal protection elements, in addition to offering training to employees so that they know the objectives that they wish to achieve, specifically, those related to the variable under study. Likewise, it is proposed to create and implement occupational safety and health programs that respond to these needs.
Keywords: Occupational health; occupational risk; safety at work; planning; management; organization; direction; public university